Expression of TPM1κ, a Novel Sarcomeric Isoform of the TPM1 Gene, in Mouse Heart and Skeletal Muscle. (24th April 2014) - Dube, Syamalima; Panebianco, Lauren; Matoq, Amr A.; Chionuma, Henry N.; Denz, Christopher R.; Poiesz, Bernard J.; Dube, Dipak K.
Abstract : We have investigated the expression of TPM1 α and TPM1 κ in mouse striated muscles. TPM1 α and TMP1 κ were amplified from the cDNA of mouse heart by using conventional RT-PCR. We have cloned the PCR amplified DNA and determined the nucleotide sequences. Deduced amino acid sequences show that there are three amino acid changes in mouse exon 2a when compared with the human TPM1 κ . However, the deduced amino acid sequences of human TPM1 α and mouse TPM1 α are identical. Conventional RT-PCR data as well as qRT-PCR data, calculating both absolute copy number and relative expression, revealed that the expression of TPM1 κ is significantly lower compared to TPM1 α in both mouse heart and skeletal muscle. It was also found that the expression level of TPM1 κ transcripts in mouse heart is higher than it is in skeletal muscle. To the best of our knowledge, this is the first report of the expression of TPM1 κ in mammalian skeletal muscle.